Effects of deep-sea water on training efficiency, locomotor function and respiratory metabolism in young and aged mice - Koji Fukui; Riki Takeuchi; Yugo Kato; Nozomu Takeuchi; Hirotsugu Takenaka; Masahiro Kohno (Heliyon)
Deep sea water (DSW) contains many trace minerals, and its applications, which include its use as drinking water, have gradually been expanding. Generally, humans tend to be lacking in mineral intake and deficiencies of trace minerals may increase the risk of several health problems. In recent years, the lack of exercise among the elderly has become an issue, leading to the onset of frailty and sarcopenia, which in turn increases the risk of dementia. Therefore, we investigated whether the daily intake of DSW-extract-added water (DSW; hardness 300 mg/L) impacted the training effect in aged mice. Treatment with DSW significantly induced a training effect in aged mice subjected to treadmill exercise. Locomotor function and metabolic capacity were also significantly increased in aged mice after DSW treatment. The results indicate that daily intake of DSW may enhance the training effect of exercise and affect locomotor performance.